Acute Renal Failure due to a Tobramycin and Vancomycin Spacer in Revision Two-Staged Knee Arthroplasty - Ronak A. Patel; Hayden P. Baker; Sara B. Smith (Case Reports in Nephrology)
Two-stage revision total knee arthroplasty (TKA) is the standard of care for prosthetic joint infections. The first stage involves removal of the infected prosthesis and placement of an antibiotic impregnated cement spacer; following a period ranging from 4 weeks to 6 months, the spacer is then removed and replaced with a permanent prosthesis. The advantage to this approach is that antibiotic impregnated spacers provide supratherapeutic levels in the joint without toxic accumulation in serum. However, it remains important for physicians and pharmacists to be aware of antibiotic associated complications in knee revisions. We present a case of a two-stage revision total knee arthroplasty in which a cement antibiotic spacer caused acute renal failure and ultimately resulted in persistent chronic kidney disease without hemodialysis at 2 months’ follow-up. Our case reports the third highest serum tobramycin (13.7 mcg/ml) and second highest serum creatinine (8.62 mg/dl) for patients experiencing ARF due to an antibiotic spacer in two-stage revision TKA.